Incidence of fractures requiring inpatient care - Somersalo, Axel (Informa Healthcare, 2014)
BACKGROUND: The overall incidence of fractures has been addressed in several studies, but there are few data on different types of fractures that require inpatient care, even though they account for considerable healthcare costs. We determined the incidence of limb and spine fractures that required hospitalization in people aged ≥ 16 years. PATIENTS AND METHODS: We collected data on the diagnosis (ICD10 code), procedure code (NOMESCO), and 9 additional characteristics of patients admitted to the trauma ward of Central Finland Hospital between 2002 and 2008. Incidence rates were calculated for all fractures using data on the population at risk. RESULTS AND INTERPRETATION: During the study period, 3,277 women and 2,708 men sustained 3,750 and 3,030 fractures, respectively. The incidence of all fractures was 4.9 per 10(3) person years (95% CI: 4.8–5.0). The corresponding numbers for women and men were 5.3 (5.1–5.4) and 4.5 (4.3–4.6). Fractures of the hip, ankle, wrist, spine, and proximal humerus comprised two-thirds of all fractures requiring hospitalization. The proportion of ankle fractures (17%) and wrist fractures (9%) was equal to that of hip fractures (27%). Four-fifths of the hospitalized fracture patients were operated. In individuals aged < 60 years, fractures requiring hospitalization were twice as common in men as in women. In individuals ≥ 60 years of age, the opposite was true.